The differences in students’ attitudes and perceptions of NEST and NNEST - Reza Anggriyashati Adara (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2019)
Students might have different attitudes and perceptions of different types of teachers. The present study aims to analyse the differences in students’ attitudes as well as perceptions toward two different types of teachers; NEST (Native English Speaking Teachers) and NNEST (Non-Native English Speaking Teachers). The present study used a mixed method approach by distributing a set of questionnaires to sixty junior high school students and interviewing four of them. Despite showing relatively positive attitudes toward both teachers, the findings revealed that the participants paid more attention to NEST than NNEST. Although most participants do not think English should only be taught by NEST, there is a preference over NEST whom are considered as more effective in teaching speaking skills, pronunciation, and cultural knowledge. However, the participants show more relaxed attitudes when they were being taught by NNEST due to shared L1 as well as teachers’ knowledge in learning English as non-native speakers. In addition, NNEST were perceived as better teachers of grammar than NEST. Thus, both teachers should learn from each other to create a better learning environment for students. Besides that, teacher trainings should equip pre-service teachers with knowledge to overcome their weaknesses either as NEST or NNEST.